Flexible lot size for kanban system to reduce material overflow in hard disc assembly process - Astuti, Fatma Hermining (2015)
This research was conducted based on a case study at an electronic manufacturing company that produces hard disc. Here, Kitting is the first step in assembly process. It is initiated well before the commencement of actual production to be able to prepare and deliver the material on time. Compound/Kitting section involves the provision of all the materials needed for a particular assembly process from the Warehouse and issuing the materials to the Assembly line. The Compound/Kitting section has been always crowded with high incoming materials (overflow) such that more spaces are needed to allocate the incoming materials. Therefore, the aim of this research is to minimize the overflow of incoming materials at Compound/Kitting section. Thus, three objectives are set: (i) to identify the overflow of incoming material at Compound/Kitting section and its implication to the performance of the subsequent production process, (ii) to analyze the demand changes patterns at production shop floor and its effects to the Compound/Kitting section and Assembly line performances, and (iii) to propose and evaluate the Flexible Lot Size for Kanban System to minimize the overflow of incoming materials. In this regard, Lean Manufacturing tools and techniques such as Value Stream Mapping (VSM) and Kanban system have been adopted to overcome the overflow of incoming materials. The constructed current VSM shows the lack of ordering system and the uncertain changes in demand cause to the overflow of incoming materials. Motivated by these factors, a Flexible Lot Size (FLS) for Kanban System is proposed to resolve the phenomenon. The FLS was modeled using simulation software. It begins by developing the current production simulation model that validated by the historical data of production input and output at Warehouse, Compound/Kitting section and also Assembly line section. In this study, the demand was classified into three categories: low, medium, and high. This research conclude that VSM is an effective tool to map the problems, while the FLS was able to provide the optimum Kanban number and lot size for the case of uncertain demand. In conclusion, a smooth production flow between Warehouse, Compound/Kitting section and Assembly line section can be sustained using the JIT concept “the right quantity at the right time”. In this way, the overflow of incoming materials at Compound/Kitting section has been decreased till 87.3 percent.